Sexual Victimization Involving Solo Female Offenders: a Crime Script Approach - Chopin, Julien (Crime & delinquency, 2023)
This study aims to provide a theoretically grounded analysis of the crime-commission process of solo females involved in sexual offending, using crime scripts. The sample includes 93 cases of sexual assaults perpetrated by female offenders in an extrafamilial context. Latent class analysis was used to identify the scripts involved in female sexual offending as well as to explore the relationship between each step of the crime-commission process. Also, additional variables related to victim, offender, and location characteristics were used to test the external validity of the model. Results suggest four different scripts used by females: Daytime Indoor, Coercive Outdoor, Coercive Indoor, and Nighttime Indoor. Theoretical and practical implications are discussed.